2015
DOI: 10.3402/ejpt.v6.24981
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder according to DSM-5 and DSM-IV diagnostic criteria: a comparison in a sample of Congolese ex-combatants

Abstract: BackgroundCompared to DSM-IV, the criteria for diagnosing posttraumatic stress disorder (PTSD) have been modified in DSM-5.ObjectiveThe first aim of this study was to examine how these modifications impact rates of PTSD in a sample of Congolese ex-combatants. The second goal of this study was to investigate whether PTSD symptoms were associated with perpetrator-related acts or victim-related traumatic events.MethodNinety-five male ex-combatants in the eastern Democratic Republic of Congo were interviewed. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Indirect exposure can lead to secondary traumatic stress: the symptoms of PTSD are present, but are considered secondary because the exposure was indirect [ 2 ]. The current definition of a traumatic event in PTSD in DSM5 has merged direct and indirect exposure, making work related indirect exposure a potentially traumatic event [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect exposure can lead to secondary traumatic stress: the symptoms of PTSD are present, but are considered secondary because the exposure was indirect [ 2 ]. The current definition of a traumatic event in PTSD in DSM5 has merged direct and indirect exposure, making work related indirect exposure a potentially traumatic event [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We did not investigate what our results would have been with the DSM‐5 criteria. Indeed, DSM‐4 and DSM‐5 PTSD criteria are different, and some studies show that DSM‐5 diagnostic rules increase PTSD rates, while others show that there are discrepancies (some diagnosed with one set of criteria are not diagnosed with the other) …”
Section: Discussionmentioning
confidence: 99%
“…Further research is therefore needed to examine whether positive endorsements of symptoms from all six (in case of the 6-factor models) or seven (in case of the Hybrid model) symptom clusters would be needed for a diagnosis of PTSD, since several studies have shown that changes in diagnostic criteria and dimensional structure have implications to PTSD prevalence rates estimations (e.g., Hansen, Hyland, Armour, Shevlin, & Elklit, 2015; Schaal, Koebach, Hinkel, & Elbert, 2015). …”
Section: Discussionmentioning
confidence: 99%